2020
DOI: 10.1029/2020jc016464
|View full text |Cite
|
Sign up to set email alerts
|

El Niño‐Southern Oscillation Impacts on Global Wave Climate and Potential Coastal Hazards

Abstract: Long-term variability of the wave climate induces interannual to multidecadal fluctuations of the shoreline (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 57 publications
(133 reference statements)
2
24
0
Order By: Relevance
“…Waves occur naturally in all coastal areas; however, the patterns of wave persistence, intensity, and direction are changing because of human activities. These changes are mainly associated with local infrastructure, dredging activities, sea-level rise, and the expansion of the tropics (e.g., changes in power, persistence, and direction of the waves [18]).…”
Section: Driversmentioning
confidence: 99%
“…Waves occur naturally in all coastal areas; however, the patterns of wave persistence, intensity, and direction are changing because of human activities. These changes are mainly associated with local infrastructure, dredging activities, sea-level rise, and the expansion of the tropics (e.g., changes in power, persistence, and direction of the waves [18]).…”
Section: Driversmentioning
confidence: 99%
“…This may be because the El Niño and La Niña events have a slight time lag (Figure 3). Ref [69] showed that the ONI explains better the multiannual wave climate variation in the tropical Pacific. Thus, further analyses are needed to see whether there are any relationships with local vulnerability as already described for climatology [70,71], fisheries [72], or nutrients [73].…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The interannual variability of the global wave climate is principally governed by ENSO (Barnard et al., 2015; Odériz, Silva, Mortlock, & Mori, 2020; Stopa & Cheung, 2014). The ENSO signal can be either amplified or dampened by extratropical, multidecadal signals, such as the PDO (Newman et al., 2003) and SAM (Clem et al., 2020), that in turn impact ocean wave conditions (Bromirski et al., 2013; Godoi & Júnior, 2020; Hemer et al., 2010; Odériz, Silva, Mortlock, & Mori et al., 2020). SAM is also the dominant large‐scale pattern of the Southern Ocean (Wang & Cai, 2013).…”
Section: Tropical and Extratropical Natural Variabilitymentioning
confidence: 99%
“…This may be associated with above‐average tropical cyclone activity in the Pacific (Bell & Chelliah, 2006) during El Niño, and we should be cautious of taking only this averaged WCT for representing the region. On the other hand, the ENSO‐negative phase weakens the Icelandic Low (Odériz, Silva, Mortlock, & Mori, 2020), and when is coupled with SAM a PDO, influences the dynamics of the polar WCT in the North Atlantic ( ∼7 kW/m).…”
Section: Tropical and Extratropical Natural Variabilitymentioning
confidence: 99%